Analisis Nilai Religius dalam Novel Assalamualaikum Calon Imam Karya Ima Madaniah - Nurhasanah Nurhasanah; Suci Novira Putri; Nabila Syafri Falencia; Sadira Argiyanti; Salsabila Aprila Hadi; Farel Olva Zufe (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The novel Assalamualaikum Calon Imam by Ima Madaniah contains religious values ​​that are fading among modern teenagers. This study identified five dimensions: steadfastness in tahajjud prayer, tranquility in prayer, balance in Muslim women, patience, and gratitude. Using a descriptive qualitative method with a structural approach. The quotation data were analyzed inductively with triangulation of Endraswara's theory (2016). The results show that the novel is effective in shaping adolescents' spiritual resilience against modern temptations, academic pressure, and Generation Z materialism. This research enriches the study of Islamic literature and is recommended as high school teaching material.